Elevated soluble TNFα levels and upregulated TNFα mRNA expression in purified peripheral blood monocyte subsets associated with high-grade hepatocellular carcinoma - C. Martín-Sierra; R. Martins; M. Coucelo; A. M. Abrantes; R. C. Oliveira; J. G. Tralhão; M. F. Botelho; E. Furtado; M. R. Domingues; A. Paiva; P. Laranjeira (BMC, 2020)
Abstract Background Chronic inflammation is involved in the initiation and progression of various cancers, including liver cancer. The current study focuses on the characterization of the peripheral immune response in hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) patients, before and after surgical procedure, in order to assess the effect of tumor resection in the immune system homeostasis and to determine possible prognostic factors associated with high-grade tumors. We developed a whole-blood assay to monitor immune alterations and functional competence of peripheral monocytes in a group of 10 healthy individuals (HG), in 20 HCC patients and 8 CCA patients, by multi-color flow cytometry, qRT-PCR, and ELISA techniques. Results The qRT-PCR analysis showed an upregulation of TNFα expression by classical and intermediate monocytes purified from HCC patients presenting tumors in grade G3-G4 as compared to G1-G2 HCC patients. Moreover, ELISA assay confirmed elevated serum levels of TNFα in G3-G4 compared to G1-G2 HCC patients. A significant decrease of circulating non-classical monocytes was detected in both CCA and HCC patients before and after surgical procedure. In addition, a functional defect in circulating classical and intermediate monocytes was observed in both groups of cancer patients when compared to the HG, with partial recovery after the surgical intervention. Conclusions This integrated analysis permitted the identification of altered functional competence of monocyte subsets in CCA and HCC patients. In addition, our results point to a potential role of TNFα as a prognostic peripheral biomarker in HCC patients, indicating the presence of high-grade tumors that should be further validated.